PENGEMBANGAN BAHAN AJAR KOMIK CERITA RAKYAT BEE LODO UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI GOTONG ROYONG DI KELAS IV SD INPRES MAPOLI - Bara, Mercy; Marselina Nitte, Yulsy; Margarita Anastasia Hendrik, Hingrida (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Bara, Mercy, 2026. Development of Bee Lodo Folklore-Based Comic Teaching Materials to Improve Students’ Learning Outcomes on the Mutual Cooperation Topic in Grade IV of SD Inpres Mapoli. Supervisors: Yulsy Marselina Nitte, S.H., M.Pd. and Hingrida Margarita Anastasia Hendrik, S.Pd., B.Ed., M.M. Elementary School Teacher Education Study Program, Faculty of Teacher Training and Education, Citra Bangsa University Kupang. Folklore-based comic teaching materials play an important role in creating engaging, contextual, and meaningful learning experiences for elementary school students. The development of Bee Lodo folklore-based comic teaching materials is expected to support teachers and fourth-grade students of SD Inpres Mapoli in improving students’ understanding and learning outcomes on the topic of Mutual Cooperation in Pancasila Education. This study aimed to determine the validity, practicality, and effectiveness of the Bee Lodo folklore-based comic teaching materials in improving students’ learning outcomes. This study employed a Research and Development (R&D) method using the ADDIE model consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The Analysis stage was conducted to identify teachers’ needs, students’ characteristics, and learning problems. The Design stage focused on designing the Bee Lodo folklore-based comic teaching materials. The Development stage involved product creation and validation by material, language, and media experts. The Implementation stage was carried out through a limited trial involving 19 fourth-grade students of SD Inpres Mapoli. The Evaluation stage was conducted to determine the quality of the product through learning outcome tests and teacher and student response questionnaires. The research instruments included validation sheets, learning achievement tests, and teacher and student response questionnaires. Data analysis techniques included validity testing, reliability testing, normality testing, linearity testing, homogeneity testing, hypothesis testing using the paired sample t-test, and N-Gain analysis. The results showed that the Bee Lodo folklore-based comic teaching materials were feasible for use in learning activities. Material expert validation reached 98.33% (very valid), language expert validation reached 97.72% (very valid), and media expert validation reached 97.50% (very valid). Teacher responses reached 100% (very good), while student responses reached an average of 97.26% (very good). The effectiveness of the teaching materials was demonstrated by the improvement of students’ learning outcomes, with the average pretest score increasing from 69.21 to 90.26 in the posttest. The N-Gain score of 0.7011 was categorized as high. Therefore, the Bee Lodo folklore-based comic teaching materials were proven to be valid, practical, and effective in improving students’ learning outcomes on the topic of Mutual Cooperation.